Pertanggung Jawaban Pidana Korporasi Terhadap Pemberantasan Tindak Pidana Korupsi - Prakasa, Ragil surya; Husein, Husein; Delvia, Delvia; Salsabila, Qhas Karina; Alif, Rahmat Syauqi (eScience Humanity Journal, 2024)
The development of science and technology and the current unstoppable stream of globalization not only has a positive but also often has a negative impact,for example by the existence of “Crime globalization” and the development of quality (modus operandi) and quantity of criminal acts by corporation.The Problem in this article is How the accountability of corporate criminal law is in theeffort to tackle corruption in the future.The research method used in this article is normative juridical.The result of the study concluded that in the corporate criminal liability policy in the effort to tackle corporate crime in the effort to tackle corruption at the moment there are several weaknesses regarding when corporations commit criminal acts of corruption and criminal sanctions.Therefore for the future criminal responsibility policy of the corporation the explain the provisions and law enforcers can implement it.